2008
DOI: 10.1177/0883073808320620
|View full text |Cite
|
Sign up to set email alerts
|

Comparison in Obstetric Management on Infants With Transient and Persistent Obstetric Brachial Plexus Palsy

Abstract: The outcome of obstetric brachial plexus palsy depends on the severity of the lesion of the nerve fibers. The aim of the prospective study is to evaluate if differences in force used in downward traction on the fetal head correlate to the number of nerve roots affected. At final neurological examination at 18 months of age, complete neurological recovery occurred in 80 of 98 children (82%). Downward traction of the fetal head was applied more often and with greater force in the group with persistent damage. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…20 That the traction was usually downward comports with the 60% right-sided injury in our population as left occipitoanterior or left occipitotransverse presentation occurs more frequently (less than twice as often) than right occipitoanterior or right occipitotransverse.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…20 That the traction was usually downward comports with the 60% right-sided injury in our population as left occipitoanterior or left occipitotransverse presentation occurs more frequently (less than twice as often) than right occipitoanterior or right occipitotransverse.…”
Section: Discussionmentioning
confidence: 99%
“…With 104 infants, Poggi et al 24 concluded that operative delivery does not worsen the degree of injury. Mollberg et al 20 found a correlation between the amount of downward traction and injury severity. No study has systematically examined the relationship of obstetric factors and birthweight with the neurological severity of the OBPL.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3]5,6,16,21,23,26,30,32,34,35,38,41,[47][48][49][57][58][59]62,65 Cases of macrosomia, clavicle facture, and humerus fracture were identified within all newborn records (Appendix 2). Classifications of heavy for gestational age (not macrosomia), fetal or birth asphyxia, and intracranial nontraumatic hemorrhage were available for Ontario records only.…”
Section: Variablesmentioning
confidence: 99%